Worker churn in the cross section and over time: New evidence from Germany - Bachmann, Rüdiger; Bayer, Christian; Merkl, Christian; Seth, Stefan; Stüber, Heiko; Wellschmied, Felix (Journal of Monetary Economics, 2021)
Worker churn is procyclical in the German labor market. We study the plant-level connection of churn and employment growth using the new Administrative Wage and Labor Market Flow Panel from 1975 to 2014. Churn is V-shaped in employment growth. Through analyzing this pattern by worker skill, age, and tenure, we establish that churn is unlikely to result from plant reorganization but rather from uncertainty about match quality. In a dynamic labor demand framework with a time-to-hire friction, churn can be interpreted as a manifestation of idiosyncratically stochastic separation shocks. These shocks become larger and more predictable during booms, leading to procyclical churn.
CRIS-Team Scopus Importer:2020-06-26
Keywords: Aggregate fluctuations; Employment growth; Job flows; Job-to-job transitions; Labor demand; Separation shocks; Worker churn; Worker flows